2022
DOI: 10.1155/2022/8968793
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of a New Predictive Model for Insulin Resistance based on 2 Chinese Cohorts: A Cross-Sectional Study

Abstract: Background. Visceral adiposity plays a key role in the development of insulin resistance (IR), so surrogate index that can indicate visceral obesity may have higher predictive value for IR. This study aimed to establish and validate a new predictive model including indicator of visceral obesity for IR. Methods. The study population consisted of two cohorts. The derivation cohort was a group of 667 patients with newly diagnosed type 2 diabetes and the population undergoing a routine health checkup was the valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It is well known that visceral adiposity plays a key role in the development of IR. Therefore, using surrogate indicators that include visceral fat may have a higher predictive value than indicators that use only biochemical measures and this conjecture has been con rmed in previous study [19] . Then we conducted an analysis using the New Model with the VSR, resulting in similar results as HOMA-IR, with the VSR being an independent risk factor for the New Model, while also having the same strength of predictive power for the new model resistance.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is well known that visceral adiposity plays a key role in the development of IR. Therefore, using surrogate indicators that include visceral fat may have a higher predictive value than indicators that use only biochemical measures and this conjecture has been con rmed in previous study [19] . Then we conducted an analysis using the New Model with the VSR, resulting in similar results as HOMA-IR, with the VSR being an independent risk factor for the New Model, while also having the same strength of predictive power for the new model resistance.…”
Section: Discussionsupporting
confidence: 61%
“…Research showed visceral adiposity is crucial in the evolution of IR, and vicarious indicators that re ected visceral obesity may have a higher predictive value for IR. Therefore, our team had established and validated a new IR prediction model [19] that includes visceral obesity indicators, and con rmed its predictive value by comparing it with other vicarious indicators. The formula used to calculate the New Model was (0.0293 * age + 1.4892 * Ln VFA + 0.4966 * Ln TG + 2.784 * Ln FPG + 0.6906 * Ln ALT)/2, and the cut-off value for the New Model was 8.18.…”
Section: Calculation and De Nition Of Multi-organ Irmentioning
confidence: 99%